Galectin-3 Marker Expression in Renal Cell Carcinoma and Correlation with patient Clinicopathologic Factors: A cross-sectional study - Ghodsieh Kamrani; Reza Havaspour; Mohammad Ranaee; Hamid Shafi; Hoda Shirafkan; Mohammad Ebrahim Sohrabi; Davoud Jahansouz (Babol University of Medical Sciences, 2025)
Background: Renal Cell Carcinoma is one of the most common malignancies worldwide. To date, multiple attempts had been made to accurately diagnose it and predict its behavior. One of the most intriguing biomarkers that have been assessed since 90s, is galectin-3. This study aimed to increase the prior knowledge of galectin-3 expression association with patient's clinicopathologic factors. Methods: In this single-center cross-sectional study, 71 patient samples from hospital archive were assessed for galectin-3 expression by immunohistochemistry assay. Pathologic slides were evaluated for histologic subtype, grade, stage, tumor size, presence of necrosis, and invasion of the renal vein. By adding cytoplasmic staining score to the color intensity score, a final score was recorded as galectin-3 positivity score. Results: 88 pathological slides of patients with confirmed RCC were screened and 71 were finally assessed. The mean age of the patients was 58.52 years (lowest 30 and highest 87). 67.6% were males and 32.4% were females. 68% of tumors were clear cell carcinoma, and only one oncocytoma was present. All 9 chromophobe cases showed a strong galectin-3 expression. Except for female gender (47.8% vs 18.8% in men; P=0.01), no statistically significant association was found between patient age, tumor grade, tumor size, tumor stage, and renal vein invasion with the level of galectin-3 expression. Conclusion: Considering the contradictory findings between this study and other similar studies, it can be concluded that the physiological role of galectins is very complex and the need for larger and more comprehensive evaluations is felt.